Cybersecurity High School Innovations: A Path for Educators to Teach Cybersecurity Courses in their Schools (Journal of The Colloquium for Information Systems Security Education, 2025)
There remains a significant unmet demand for cybersecurity professionals nationwide. Many solutions have been forwarded, but more are needed. Improving opportunities within higher education institutions is important and a critical component of addressing this unmet need, but may do too little too late for many potential cybersecurity professionals. This paper examines the development of an innovative program designed to address this challenge by providing opportunities to secondary educators of all backgrounds. Participants are given an opportunity to learn about cybersecurity and how to bring what they learn back to their own schools and teach it to their students as a standalone course. The program provided a remote component in preparation for an intensive in-person summer summit where participants were brought together at one or more locations. During that time, they would hear from experts in academia, industry, and the military, as well as have an opportunity to practice what they learned through various hands-on labs and activities. Participants from the first year were invited back the second year for a more challenging and advanced experience. During the third year, first and second year participants were invited back such that there were three levels of participants. This paper reports on the findings of this innovative program and provides recommendations for future iterations of similar programs based on lessons learned.
Keywords: cybersecurity; secondary education; curriculum; courses